Mendedah Lokalitas, Menuju Interseksionalitas: Suatu Usulan Heuristik Lintasan Berteologi dalam Konteks Bagi Kaum Tionghoa-Injili Indonesia Lewat Kacamata Interseksionalitas - Adrianus Yosia (Indonesian Journal of Theology, 2020)
This article discusses the utility of intersectional theology for understanding the contextual plurality of social identity within an Indonesian Sino-evangelical frame. My claim will be that the very multiplicity of social identity found in Sino-evangelical communities in Indonesia, which arises from the context of the May 1998 riots, serves as a theological resource that takes form according to certain heuristic trajectories. These trajectories stem from four well-attested characteristics of the Evangelical category itself, which in turn can be read through intersectional lenses. To achieve such an aim, I first explore the notion of plural identity vis-à-vis the label of Sino-evangelical in general. The essay then moves to discuss intersectional theology in light of what is characteristic about the category, Evangelical. Afterward, I explicate a key social context for the Sino-evangelical community, namely, the May 1998 riots. In the final section, I construct certain theologically heuristic trajectories according to an intersectional theological reading of the Sino-evangelical community, which is then framed according to four dimensions of David W. Bebbington’s (Evangelical) quadrilateral: conversionism, activism, biblicism, and crucicentrism.